2023
DOI: 10.3390/ma16072776
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental and Numerical Analysis of Glued Laminated Beams Strengthened by Pre-Stressed Basalt Fibre-Reinforced Polymer Bars

Abstract: Damage often develops in glued laminated timber members under high bending loads due to natural defects in the timber, which results in their low load-bearing capacity and stiffness. In order to improve the bending mechanical properties of glulam beams, a new type of longitudinal glulam reinforcement with pre-stressed basalt fibre-reinforced polymer composites (BFRP) was developed using the Near Surface Mounted (NSM) technique. The strengthening method consisted of two pre-stressed BFRP bars glued into the gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…However, for steel bars, this load capacity increased by 59.74% and stiffness by 31.08%. The degree of reinforcement was defined as the percentage increase in strength of reinforced beams relative to unmodified reference beams (Table 2) [28,41]. Determined as the cross-sectional area without reinforcement in relation to the cross-sectional area of the reinforcement.…”
Section: Load-deflectionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for steel bars, this load capacity increased by 59.74% and stiffness by 31.08%. The degree of reinforcement was defined as the percentage increase in strength of reinforced beams relative to unmodified reference beams (Table 2) [28,41]. Determined as the cross-sectional area without reinforcement in relation to the cross-sectional area of the reinforcement.…”
Section: Load-deflectionmentioning
confidence: 99%
“…Studies of plant fibres (e.g., flax) have shown that, as a single fibre, they have comparable specific mechanical properties (e.g., specific tensile strength and stiffness) compared to man-made glass fibres [8]. However, this is misleading, as the length of natural fibres is limited when a carbon or glass fibre can be manufactured to have infinite length [26][27][28]. Fibre-reinforced wood composites have found wide application in many industrial fields.…”
Section: Introductionmentioning
confidence: 99%
“…The same approach was used in papers [8,60] based on the test results presented in [61]. This approach was also used for glued laminated timber and solid beams in papers [62,63]. The LVL laboratory tests presented by van Beerschoten [64] demonstrated that in LVL, with all veneers glued lengthwise, tangential stiffness was only slightly higher than radial stiffness.…”
Section: The Numerical Models Of the Lvl Panelsmentioning
confidence: 99%
“…Unfortunately, a limitation of GFRP is its elastic modulus, which is significantly lower than that of structural steel, leading to an increased deformation of GFRP-reinforced components [11,12]. Much research has also been carried out using CFRP, BFRP, GFRP or steel fibers in various forms, including in tapes, mats and rods or in various other forms and characteristics of FRP, such as in construction, structures, reinforcing solid wood beams, wedge-jointed solid beams, laminated veneer lumber (LVL), cross-laminated timber (CLT) and glued laminated timber (GLT) beams-see [13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Modern solutions also include engineered products such as glulam, formed from layers of graded structural lumber [13][14][15][16][17][18][19][20]. The advantages of these products include the use of shorter pieces of timber to form full-length laths using structural adhesives.…”
Section: Introductionmentioning
confidence: 99%